2013
DOI: 10.2147/ijn.s44211
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously delivered graphene nanosheets and multiwalled carbon nanotubes induce site-specific Th2 inflammatory responses via the IL-33/ST2 axis

Abstract: Abstract:Carbon-based nanomaterials (CBN), such as graphene nanosheets (GNS) and multiwalled carbon nanotubes (MWCNT), have been proposed for potential nanomedicine applications such as biomedical devices and carriers for drug delivery. However, our current understanding regarding the systemic toxicity of these CBN through intravenous (iv) injection is limited. In this study, we compare the immune response resulting from GNS and MWCNT exposure. We hypothesize that iv administration of GNS and MWCNT would resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…119 A recent study concluded that intravenously administered CNT and graphene nanosheets induce T helper 2-immune responses via the IL-33/ST2 axis, since responses were partially attenuated in ST2-deficient mice. 120 In the case of NP, immune effects are influenced by particle size and shape. Intratracheal administration of agglomerated CNT results in granuloma formation 121 , whereas dispersed CNT (e.g., coated by surfactant) results in more diffuse fibrosis.…”
Section: Biological Effectsmentioning
confidence: 99%
“…119 A recent study concluded that intravenously administered CNT and graphene nanosheets induce T helper 2-immune responses via the IL-33/ST2 axis, since responses were partially attenuated in ST2-deficient mice. 120 In the case of NP, immune effects are influenced by particle size and shape. Intratracheal administration of agglomerated CNT results in granuloma formation 121 , whereas dispersed CNT (e.g., coated by surfactant) results in more diffuse fibrosis.…”
Section: Biological Effectsmentioning
confidence: 99%
“…The zeta potential of the particles in (S)-MWCNTs suspension was −57.3 mV with a mean hydrodynamic size of 915 nm. MWCNTs suspended in the DPPC, serum albumin and sterile phosphate buffered saline medium [(D)-MWCNTs] was characterized previously by Wang et al [29] with a zeta potential of −20.8 mV with a mean hydrodynamic size of 793 nm.…”
Section: Resultsmentioning
confidence: 99%
“…A MWCNT suspension of 150 μg/ml was made with DPPC/RSA and the mixture was cup-horn sonicated using a Misonix ultrasonic liquid processor -1510R-MTH (Branson Ultrasonics Corp. Danbury, CT, USA) at 65% amplitude for 2 minutes. This intravenous suspension will be referred to as “(D)-MWCNTs” and was previously described by Wang et al [29]. …”
Section: Methodsmentioning
confidence: 99%
“…This type of contact also leads to systemic exposure to and organ accumulation of the injected material via vascular distribution. It was also noted that the tissues mount a tissue specific “nanoparticle-induced inflammatory response” in reaction to this direct interaction and deposition 38 ; this response is more detrimental with materials of a higher aspect ratio 38 . Evaluation of alveolar regions of the lung after pulmonary exposures document MWCNT deposition and penetrations 39 ; it is reasonable to suspect that the endothelial vascular lining would suffer the same fate after intravenous exposure, ENM deposition, and speculated penetration.…”
Section: Alternate Routesmentioning
confidence: 99%